THE FUNCTION OF QUANTITATIVE MEANS OF EXPRESSION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article,we study the language category of quantity, the combining properties of numerales . A great place is given to numerals , their values in speech. The article also analyzes the problem of number , the system of quntitative meanings in the grammatical structure of language , vocabulary, in different linguistic genres, in speech.